EVALUATION OF SUPPLY CHAINS BASED ON SENSE AND RESPOND AND SUSTAINABLE COMPETITIVE ADVANTAGES (SCR) - Nikookar, Hassan (My University, 2013)
Due to globalization of business environment and tendency of companies to be more lean and agile, today supply chains are more vulnerable to disruptions. The most prominent thing affected by disturbances is productivity and consequently financial capabilities of the company. The vital factor of a company that can help tackle disturbances is resiliency capability of its supply chain i.e. the capability of supply chain to absorb disruption and moving back to its original state on more desirable one very soon. This thesis aims at utilization of sense and responds methodology, as one of the valuable tools to identifying weak points and critical attributes in a business process, to identify critical attributes contributing toward supply chain resiliency. It may help managers to explore supply chain threats from resiliency point of view to achieve more reliable supply chain. A case study was performed in a part of Iranian automotive supply chain consist of one manufacturer and four suppliers was revealed that the main issue in Iran automotive industry regarding resiliency is related to visibility through supply chain. The main concentration of this paper was automotive supply chain. To establish more reliable and meaningful conclusion, the need of more empirical investigation is significant.
Keywords: Resilient supply chain; Disruptive event; automotive industry; Sense and Respond; Case study; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|